XoveTIC 2021 - de Moura, Joaquim; González, Marco A.; Pereira Loureiro, Javier; Penedo, Manuel G. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This volume of Engineering Proceedings gathers papers presented at XOVETIC2021 (A Coruña, Spain, 7-8 October 2021), a conference with the main goal of bringing together young researchers working in big data, artificial intelligence, the Internet of Things, HPC (High-performance computing), cybersecurity, bioinformatics, natural language processing, 5G and others areas from the field of ICT (Information Communications Technology) and offering a platform to present the results of their research to a national audience and Portugal. This fourth edition aims to serve as the basis of this event, which will be consolidated over time and acquire international projection. Financial support from Vice-rectorate for Science Policy, Research and Transfer of Universidade da Coruña and Consellería de Cultura, Educación e Universidade of the Xunta de Galicia (Convenio I+D+i Centro de investigación de Galicia 2019-2022) and the European Union (European Regional Development Fund-ERDF) is gratefully acknowledged.